Professional Services Offered By Community Pharmacists And Challenges In Managing Community Pharmacies: Views From Community Pharmacy Practitioners In The State Of Sarawak - Kho, Boon Phiaw (2018)
The focus of community pharmacies worldwide is gradually shifting towards service-based. Unfortunately, various management challenges delay this progression, especially in developing countries like Malaysia. Dimension of challenges faced in the management of community pharmacies is poorly articulated in the literature. The aims of this study were to explore the current status of professional pharmacy services provision and management challenges faced by community pharmacists in Sarawak, Malaysia. A mixed-methods design comprising qualitative (Phase 1) and quantitative (Phase 2) components was used. In Phase 1, semi-structured interviews were carried out with community pharmacists practising in Sarawak. Purposive and snowball sampling techniques were employed to ensure a diverse group of informants, with data saturation achieved after 20 interview sessions. Interviews were audio-recorded and transcribed verbatim, with the resultant data analysed using thematic analysis. Eleven major themes were identified. Professional pharmacy service provision was influenced by both respondents’ intrinsic motivations and business considerations. Intra-organisational constraints faced include lack of time, personnel and physical space, whereas cultural issues, uncommitted customers, stock availability and price issues were the extra-organisational barriers. Market demand influenced respondents’ plans for further service expansion.